Тенденции развития образования на тюркских языках в коммунистической Румынии - Сейдаметов, Э.Х. (Культура народов Причерноморья, 2013)
В статье исследован вопрос о тенденциях развития образования на тюркских языках в
коммунистической Румынии. Данная тема является новой в отечественной историографии, получила
фрагментарное освещение в работах зарубежных исследователей. В результате анализа показаны
изменения, которым подверглось образование на родном языке крымских татар и турок, проживающих
в Румынии с установлением во второй половине 1940-х гг. коммунистической власти. У статті досліджено питання про тенденції розвитку освіти на тюркських мовах у
комуністичній Румунії. Дана тема є новою у вітчизняній історіографії, отримала фрагментарне
висвітлення у працях зарубіжних дослідників. У результаті аналізу показані зміни, яким піддалося
освіту рідною мовою кримських татар і турків, що проживають в Румунії з встановленням у другій
половині 1940-х рр. комуністичної влади. The article deals with the tendency of educational development in the Turkic languages in Communist
Romania. This subject is new in the national historiography and it is partially investigated in the works of
foreign researchers. The analysis results show the changes that occurred in the native language education of the
Crimean Tatars and Turks living in Romania where the Communist authorities established their government in
the second half of the 1940s. Three main stages are identified. The first stage (1948 – early 1950s.) is
characterized by development of separate Tatar and Turkish schools, which were not differentiated by ethnicity
in the previous (royal) period.
The second period (late 1950s – late 1960s.). During these years the Romanian government headed for
Romanization. The consequences of this policy was the closure of educational establishments, national and
cultural societies and clubs, the suspension of periodicals’ editions as well as the termination of newspapers and
magazines issues.
The third period (1970s - 1980s.) is characterized by a partial resumption of the Turkish language lessons in
some primary schools, establishment of publishing industry by the Crimean Tatars in the mother-tongue and the
Turkish languages.